Deprescribing and polypharmacy in an aging population - Elbeddini, Ali (Academic Press, an imprint of Elsevier, 2023)
"Deprescribing and Polypharmacy in an Aging Population supports healthcare professionals across global healthcare institutions in reducing polypharmacy-related drug replated problems (DRPs) by working with patients, families, interprofessional healthcare professionals, and educational institutions to develop, implement, test, improve upon, and educate on strategies for deprescribing and optimizing patient safety. Polypharmacy, the use of multiple medications at the same time by one person, is very common in various patient populations, including those who lack primary physicians, patients with mental health conditions, patients with multiple chronic conditions, and in the aging population."--publisher website.